Nocturnal distance sampling all‐terrain vehicle surveys for nonbreeding rails - Auriel M. V. Fournier; David G. Krementz (Wildlife Society Bulletin)
ABSTRACT Rails (Family: Rallidae) are among the most difficult birds to detect. Although methods have been developed to optimize detection during the breeding season, there is no current suitable survey method for the nonbreeding season. Low detection of rails and lack of suitable methods limit monitoring efforts and examination of important questions related to rail conservation and habitat management during the nonbreeding season. We present a new survey method along with suggestions for its effective use in moist‐soil wetlands. We conducted nocturnal surveys during the autumns 2012–2015 in Missouri, USA, to detect sora (Porzana carolina) using hierarchical generalized distance sampling along transects that we traveled while riding all‐terrain vehicles at night. We evaluated assumptions of our survey method by examining the response by radiomarked sora to survey vehicles and comparing survey counts between surveys on the same night. These surveys produced sora density estimates with error that can be used to address conservation and management questions such as habitat use and migratory timing. Published 2017. This article is a U.S. Government work and is in the public domain in the USA.